1931
DOI: 10.1021/ja01356a052
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of the Normal Paraffin Hydrocarbons, Pentane to Dodecane

Abstract: the cooling which is preliminary to carbonation. By so doing, the yield is improved because otherwise oxygen from the atmosphere would be pulled in and react with the Grignard reagent. In a 0.2 mole run the yield of cyclohexanecarboxylic acid based on an 80% yield of cyclohexylmagnesium bromide was 83%; and the yield of acid based on a 92% yield of cyclohexylmagnesium chloride was 93%. It is recommended that the solution be diluted with ether (300-500 cc. in a 0.2 mole run) prior to carbonation, because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1932
1932
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…The properties of the best n-dodecane from this petroleum are given in table 2, together with values previously determined for this substance by Shepard, Henne, and Midgley [7] and by Mair [8]. • These values were estimated from the vaiues observed at 25° O.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The properties of the best n-dodecane from this petroleum are given in table 2, together with values previously determined for this substance by Shepard, Henne, and Midgley [7] and by Mair [8]. • These values were estimated from the vaiues observed at 25° O.…”
mentioning
confidence: 89%
“…Shepard, Henne, and Midgley [7] prepared pure n-dodecane from a special fraction of petroleum extraordinarily high in normal paraffin hydrocarbons, by distillation, chemical treatment with chlorosulfonic acid, and redistillation.…”
Section: Review Of Earlier Investigationsmentioning
confidence: 99%
“…It is therefore advisable to describe these methods briefly at this point before proceeding to a more detailed description of the individual syntheses and purifications. 1. PURIFICATION The physical methods employed were fractional distillation and fractional crystallization.…”
Section: Methodsmentioning
confidence: 99%
“…The hexyl alcohol resulting was fractionally distilled and the portion distilling between 156°and 157°C . converted into the bromide by the hydrobromic-sulphuric acid method (9 (6,15,16) and the values obtained by Shepard For these reasons only the values of Shepard, Henne, and Midgley (1) are recorded for comparison in Table 1 . …”
Section: Zmentioning
confidence: 99%
“…Mabery and Hudson (4) used a mixture of nitric and sulphuric acids, while Aschan (5) found that chlorosulphonic acid would react less rapidly with normal and quaternary hydrocarbons than with other types of petroleum compoiunds. By means of chlorosulphonic acid Shepard, Henne, and Midgley (6) The properties (7) of the material have been reported in previous papers, together with a description of the preliminary distillation (8) BOILING RAN6E OF FRACTION IN C. which separated on cooling had physical constants which clearly indicated the presence of large quantities of w-decane. In order to isolate the n-decane from this as well as from the other cuts, a systematic fractionation by equilibrium melting was undertaken.…”
mentioning
confidence: 89%